Perilaku Pemulung tentang Demam Berdarah Dengue dengan Keberadaan Jentik Aedes Aegypti - Sulistiawati Sulistiawati; Joni Haryanto; Tintin Sukartini; Mardiana Mardiana (Jurnal Ners, 2007)
Introduction: Dengue Haemorhagic Fever is an endemic disease caused by dengue virus with Aedes aegypti as the vector. Most of waste pickers in waste goods pool refuse fogging, 3M programme and abatization, so that DHF outbreak occurs in that area every year. Larva free rate also remains under the target. Therefore, it was necessary to improve DHF relation with behaviour of waste pickers. This study was used a cross sectional design. The objective of this study was to identify waste picker’s behaviour on DHF and its correlation with the presence of Aedes aegypti larva. Method: The subjects were waste picker which live at Sidokumpul and Kebomas village. There were 36 samples which recruited by using cluster random sampling. Data were collected by using questionnaire (structured intervied) and observation, then analyzed by using Fisher’s Exact Test with significance level α≤0.05. Result: The result showed that there was not a correlation between waste picker’s knowledge with the presence of Aedes aegypti larva (p=0.236), no correlation between waste picker’s attitude with the presence of Aedes aegypti larva (p=0.422) and there was a significance correlation between waste picker’s behaviour with the presence of Aedes aegypti larva (p=0.03). Discussion: It can be concluded that there was not a correlation between waste picker’s knowledge and waste picker’s attitude with the presence of Aedes aegypti larva. Moreover, the waste picker’s behaviour has a significance correlation with the presence of Aedes aegypti larva.The waste picker should improve their participation in mosquito’s nest eradication programme.